Qira'at Sab'ah in Tahajud Prayer: A Bourdieusian Analysis of Religious Practice - Maulaya, Muhammad Dzikru Alfin; Illiyyun, Naili Nimatul; Ayun, Nurul; Masruri, Hamdan Al; Muzaki, Bagus Ahmad (Universitas Muhammadiyah Surakarta, 2026)
This study examines how the tradition of reciting the Qur'an using the seven canonical readings (Qira'at Sab'ah) during tahajud prayer at Pondok Pesantren Hamalatul Qur'an Ringinagung, Kediri, represents an example of the Living Qur'an that is, the Qur'an as a text that is not only read, but lived and practiced in everyday life. While most studies on Qira'at Sab'ah tend to focus on technical aspects of recitation or its historical development, relatively little attention has been given to how this tradition is implemented and sustained within the institutional life of Islamic boarding schools (pesantren). This research employs a qualitative approach, utilizing direct observation, in-depth interviews, and document analysis as primary methods of data collection. The analysis is framed through Pierre Bourdieu's theoretical concepts of habitus (internalized dispositions), capital (resources such as knowledge and social support), and field (social arena). The findings indicate that the practice of reciting Qira'at Sab'ah during tahajud prayer gradually forms a natural and embodied habitus among the students (santri). From Pierre Bourdieu's theoretical perspective, this study finds that the tradition of Khatam Qirā'āt Sab'ah in Tahajud prayer is socially constructed and continuously reproduced through the dialectical interplay of habitus, capital, and field within the pesantren, thereby reinforcing the Living Qur'an paradigm and demonstrating that Qirā'āt practices function not merely as devotional acts but as institutionalized and legitimized socio-religious practices. This research contributes to the mobilization of religious and intellectual capital possessed by teachers, such as Ustadz Faiq Faizin, to strengthen and legitimize this tradition within the social sphere of the pesantren. This practice not only enhances the students' memorization of the Qur'an, but also deepens their appreciation and understanding of the diversity of Qur'anic recitations.